Influenza A Viruses Replicate Productively in Mouse Mastocytoma Cells (P815) and Trigger Pro-inflammatory Cytokine and Chemokine Production through TLR3 Signaling Pathway - Meng, Di; Huo, Caiyun; Wang, Ming; Xiao, Jin; Liu, Bo; Wei, Tangting; Dong, Hong; Zhang, Guozhong; Hu, Yanxin; Sun, Lunquan (Frontiers in Microbiology, 2017)
The influenza A viruses (IAVs) cause acute respiratory infection in both humans and animals. As a member of the initial lines of host defense system, the role of mast cells during IAV infection has been poorly understood. Here, we characterized for the first time that both avian-like (α-2,3-linked) and human-like (α-2,6- linked) sialic acid (SA) receptors were expressed by the mouse mastocytoma cell line (P815). The P815 cells did support the productive replication of H1N1 (A/WSN/33), H5N1 (A/chicken/ Henan/1/04) and H7N2 (A/chicken/Hebei/2/02) in vitro while the in vivo infection of H5N1 in mast cells was confirmed by the specific staining of nasal mucosa and lung tissue from mice. All the three viruses triggered the infected P815 cells to produce pro-inflammatory cytokines and chemokines including IL-6, IFN-γ, TNF-α, CCL-2, CCL-5 and IP-10, but not the antiviral type I interferon. It was further confirmed that TLR3 pathway was involved in P815 cell response to IAV-infection. Our findings highlight the remarkable tropism and infectivity of IAV to P815 cells, indicating that mast cells may be unneglectable player in the development of IAV infection.